Cascade testing for inherited arrhythmia conditions: Experiences and attitudes of family communication approaches for a Canadian cohort. Issue 3 (14th January 2022) - Ho, Amy; Leach, Emma; Virani, Alice; Arbour, Laura; Bartels, Kirsten; Wong, Eugene K.
Abstract: Inherited arrhythmia conditions (IAC) can lead to sudden cardiac death at any age, and relatives of an affected person have up to a 50% chance of inheriting the condition and are at risk for developing features. Cascade testing is a stepwise approach for identifying relatives at risk for IACs through clinical screening and genetic testing. Early detection can reduce morbidity and mortality for affected individuals and determine potential risk mitigation strategies for relatives. However, cardiovascular genetic studies have reported an incomplete uptake of cascade testing in at‐risk relatives. We explored patient perspectives on cascade testing for IACs and alternative approaches to family communication. Twelve semi‐structured phone interviews were conducted with probands of the British Columbia Inherited Arrhythmia Program confirmed to carry a pathogenic or likely pathogenic variant in a gene associated with an IAC. Thematic analysis of transcripts through an iterative coding process revealed five main themes: (a) a stepwise approach is followed in disclosing risk to relatives, (b) relatives' autonomy in cascade testing is supported, (c) lived experience with the condition influences disclosure and uptake of cascade testing, (d) collaborative approach to informing relatives reduces negative impact of disclosure, and (e) direct contact from a healthcare provider is viewed as acceptable. The findings highlight this patient cohort's experiences and opinions with approaches to disclosure and demonstrate their understanding and acceptance of their relatives' approaches to cascade testing. In addition, while the notion of direct contact was generally accepted, a collaborative approach to contacting relatives between the proband and provider may be most effective.